Erythropoietin inhalation enhances adult canine alveolar-capillary formation following pneumonectomy - Dane, D. Merrill (Am J Physiol Lung Cell Mol Physiol, 2019)
Paracrine erythropoietin (EPO) signaling in the lung recruits endothelial progenitor cells, promotes cell maturation and angiogenesis, and is upregulated during canine postpneumonectomy (PNX) compensatory lung growth. To determine whether inhalational delivery of exogenous EPO augments endogenous post-PNX lung growth, adult canines underwent right PNX and received, via a permanent tracheal stoma, weekly nebulization of recombinant human EPO-containing nanoparticles or empty nanoparticles (control) for 16 wk. Lung function was assessed under anesthesia pre- and post-PNX. The remaining lobes were fixed for detailed morphometric analysis. Compared with control treatment, EPO delivery significantly increased serum EPO concentration without altering systemic hematocrit or hemoglobin concentration and abrogated post-PNX lipid oxidative stress damage. EPO delivery modestly increased post-PNX volume densities of the alveolar septum per unit of lung volume and type II epithelium and endothelium per unit of septal tissue volume in selected lobes. EPO delivery also augmented the post-PNX increase in alveolar double-capillary profiles, a marker of intussusceptive capillary formation, in all remaining lobes. EPO treatment did not significantly alter absolute resting lung volumes, lung and membrane diffusing capacities, alveolar-capillary blood volume, pulmonary blood flow, lung compliance, or extravascular alveolar tissue volumes or surface areas. Results established the feasibility of chronic inhalational delivery of growth-modifying biologics in a large animal model. Exogenous EPO selectively enhanced cytoprotection and alveolar angiogenesis in remaining lobes but not whole-lung extravascular tissue growth or resting function; the nonuniform response contributes to structure-function discrepancy, a major challenge for interventions aimed at amplifying the innate potential for compensatory lung growth.